“Minha tia mandou pintar mais”: a participação de crianças pequenas na educação infantil e suas influências na prática pedagógica - Campos, Rafaely Karolynne do Nascimento (2020)
This thesis presents an analysis of the participation of young children in the context of Early Childhood Education, based on the current discussions on the participation of children and their influences on pedagogical practices. It starts from the consideration of highlighting the theoretical and political needs to build and deepen contributions to the modes of participation of young children in the educational process, aiming to signal to professionals in Early Childhood possibilities of providing opportunities for participation compatible with the cultures of childhood, meeting the children's modes of expression. The research has an ethnographic perspective and is based on the contributions of the Sociology of Childhood and the assumptions of the Pedagogy of Childhood. The main purpose of this thesis is to understand how the participation of children in Early Childhood Education occurs and what are its influences on pedagogical practices. Based on this central objective, the following specific objectives were listed: a) to analyze strategies used by the teacher to include children's participation in the proposed activities; b) to describe the ways that children use to participate in the pedagogical practices addressed to them by the teacher, and c) to analyze the changes in the pedagogical practices based on the children's participation in the activities directed by the teacher. The participants were seventeen children, of both genders, aged between three and four years of age, and their teacher, in a kindergarten school in the city of Aracaju, SE, Brazil. The data were collected using participant observation, field diary/fieldnotes, photographs, and video recordings. Interest groups were also held with the children, and a semi-structured interview was conducted with the teacher. The analyses revealed that, in the group and within the studied context, there is an adult control over the children's actions in the pedagogical practice, however, even in face of this control, the children insist on reinventing such practices by presenting creative ideas based on their interests. We can say that the children do not receive passively what is imposed on them by the adult, but they participate in different ways, recreating, negotiating, transgressing, or accepting the practices that are presented to them. It leads us to reflect that the children are interested in the proposed activities, they are curious, enthusiastic, they want to participate, however, they want to participate with their ways of being, with their full bodies, not immovable, as the school requires. In this context, the investigation process attested that the logic of children's participation is different from the logic of participation proposed by the school. The data revealed a minimized and controlled participation, in which the teacher uses pedagogical strategies to insert the children in her proposals using a logic of participation different from the logic of the children's participation. It limits their bodies and, consequently, their modes of expression. From this analysis, we emphasize that the children are more likely to participate effectively when activities are not planned by the teacher, arise from unpredictability, and are developed through collaborative relationships. On this basis, we concluded that the children have skills that allow them to make enriching contributions for the improvement of pedagogical actions if we consider their modes of expression, their childhood cultures, and that, despite the constraints they suffer, they participate in different ways and rhythms of their daily lives. Therefore, it is essential for the consolidation of children as full subjects of rights, who actively participate in their daily lives, that their voices and forms of expression are accepted in the educational contexts.